Small admissions : a novel - Poeppel, Amy (New York : Emily Bestler Books/Atria, 2017)
"Kate is a young woman who is unexpectedly thrust into the cutthroat world of New York City private school admissions as she attempts to understand city life, human nature, and falling in love"--
Keywords: Young women -- Fiction; School management and organization -- New York (State) -- New York -- Fiction; Romance fiction; Romance ficiton; Fiction; Romance fiction